Dinamika Mazhab Pemikiran Ekonomi Islam Kontemporer: Integrasi Mazhab Iqtishādunā, Mainstream, dan Alternatif-Kritis dalam Kerangka Epistemologi dan Implementasi - Febri Kusuma (EL-EMIR Institute, 2026)
This study aims to analyze the differences and contributions of three schools of thought in Islamic economics—the Iqtishādunā School, the Mainstream School, and the Alternative-Critical School—and to formulate an integrative framework that can strengthen the development of contemporary Islamic economics. The research employs a qualitative approach through a literature review of primary works and academic sources. The analysis is conducted using a comparative-integrative method involving data reduction, thematic presentation, and conclusion drawing. The findings indicate that the Iqtishādunā School emphasizes normative sharia foundations and distributive justice; the Mainstream School strengthens institutional aspects through adaptation to modern economics; and the Alternative-Critical School highlights empirical evaluation of claims within Islamic economics. These three schools are complementary and cannot stand independently. This study proposes a triadic framework—sharia values, economic institutions, and scientific evaluation—as a novelty for building an Islamic economic paradigm that is more normative, operational, and evidence-based.